Clinical Assessment of an Ipsilateral Cervical Spinal Nerve Block for Prosthetic Laryngoplasty in Anesthetized Horses - Morris, Tate B.; Lumsden, Jonathan M.; Dunlop, Colin I.; Locke, Victoria; Sommerauer, Sophia; Hurcombe, Samuel D. A. (Frontiers in Veterinary Science, 2020)
The nociceptive blockade of locoregional anesthesia prior to surgical stimulation can decrease anesthetic agent requirement and thereby potential dose-dependent side effects. The use of an ipsilateral second and third cervical spinal nerve locoregional anesthetic block for prosthetic laryngoplasty in the anesthetized horses has yet to be described. Anesthetic records of 20 horses receiving locoregional anesthesia prior to laryngoplasty were reviewed and compared to 20 horses of a similar patient cohort not receiving locoregional anesthesia. Non-blocked horses were 11 times more likely to require adjunct anesthetic treatment during surgical stimulation (P=0.03) and were 7.4 times more likely to receive partial intravenous anesthesia in addition to inhalant anesthesia (P=0.01). No horse in the blocked group received additional sedation/analgesia compared to the majority of non-blocked horses (75%) based on the anesthetist’s perception of anesthetic quality and early recovery movement. No difference in recovery quality was observed between groups (P>0.99). Cervical spinal nerve locoregional anesthesia appears well tolerated and useful in reducing cumulative anesthetic agent requirement and may decrease the need for additional sedation/analgesia in horses undergoing anesthetized prosthetic laryngoplasty.